PENGEMBANGAN MODUL KOMIK FISIKA PADA POKOK BAHASAN HUKUM KEPLER DI SMA KELAS XI - Hairlinda Arini Agustin; Singgih Bektiarso; Rayendra Wahyu Bachtiar (JURNAL PEMBELAJARAN FISIKA, 2018)
Abstract The physics comic module was developed on the subject of Kepler law. Thisdevelopment is made for focusing the learning to student, so that students can learnindependently and improve the students’ imagination, also the physics learning on thesubject of Kepler law becomes more easily to be understood. The purpose of thisresearch were to know the validity and effectivity of physics comic module on thesubject of Kepler law. This research used Borg and Gall development research model.This research was conducted in SMA Nurul Islam Jember XI Grade. The data obtainedin this study are validation data. The analysis performed is validation analysis basedon expert validator and user validator, also effectiveness analysis based on audiencevalidator. The validity criteria of physics comic module was 78,75% and the effectivitycriteria of physic comic module was 71,38%. Based on these data, it can be concludedthat physics comic module was valid enough and effective enough, so can be used inteaching and learning process with a little revision.Key word: module development, physics comic, kepler’s law.